The role of NGOs in empowering Londo Coffee Farmers in Sirukam Village, Solok Regency - Nirmala, Dina; Syamsir, Syamsir (Priviet Social Sciences Journal, 2025)
This study examines the role of the Kopi Aie Langang Sirukam Social Forestry Business Group (KUPS) Non-Governmental Organization in improving the capabilities of Londo coffee farmers in Nagari Sirukam, Solok Regency. Using a qualitative descriptive approach, data were obtained through interviews, direct observations, and document reviews involving KUPS administrators, the Nagari government, the LPHN institution, the non-governmental organization KKI WARSI, and farmers. The results of this study show that KUPS has an important function as a mediator, mentor, and bridge in improving the capabilities and independence of farmers. The empowerment process is carried out through continuous training programs, intensive guidance, and institutional system development, which involves active participation to support joint marketing. KUPS initiatives have succeeded in stabilizing coffee prices, improving post-harvest processing quality, and expanding market reach through digital platforms and exhibitions. However, the implementation of empowerment faces several obstacles, such as limited facilities and equipment, dependence on external funding, and uneven levels of farmer participation. Cooperation between KUPS, the Nagari Government, LPHN, and KKI WARSI has been a major driver in strengthening farmers’ capacity and promoting sustainable local economic growth. Strengthening local institutions and developing independent funding strategies is necessary to ensure long-term sustainability and community resilience.